Exploring the Asymmetric Price Behavior of Health Care and Pharma Sector Stocks of NSE in the Pandemic Period - Muthukamu, M.; Amutha, S.; Amudha, R. (Indian Journal of Finance, 2024)
Purpose : Our research aimed to gain insights into the impact of COVID-19 on the price behavior of healthcare and pharmaceutical sector stocks in the Indian equity market. Methodology : The necessary price behavior data were gathered from the National Stock Exchange’s official website. The price behavior data of the stocks that belong to the chosen sectors was gathered for the first phase of India’s strict lockdown period, which ran from March 23 to May 31, 2020. The data were analyzed using descriptive statistical tools and econometric models such as the EGARCH (1,1) model, GARCH (1,1), ADF test, and ARCH-LM test. Findings : The pharmaceutical and healthcare sectors yielded abnormal earnings and favorable returns during the study period. The companies chosen for this analysis have performed asymmetrically during the pandemic, with the healthcare sector’s stocks yielding higher returns than the pharmaceutical sector’s stocks. Practical Implications : Exploring the price behavior of the stocks during the pandemic would help budding retail investors gain clarity to trade the stocks during the negative shocks in the market. Originality : In contrast to previous research, we have limited our investigation to examining the price behavior of equities in the pharmaceutical and healthcare sectors, which exhibit the opposite behavior from the overall market sentiment throughout the pandemic period.